The Response Regulator Slr1588 Regulates spsA But Is Not Crucial for Salt Acclimation of Synechocystis sp. PCC 6803 - Song, Kuo; Hagemann, Martin; Tan, Xiaoming; Lu, Xuefeng (Frontiers in Microbiology, 2017)
Cyanobacterial sucrose biosynthesis is stimulated under salt stress, which could be used for biotechnological sugar production. It has been shown that the response regulator Slr1588 negatively regulates the spsA gene encoding sucrose-phosphate synthase and mutation of the slr1588 gene also affected the salt tolerance of Synechocystis (Chen et al., 2014). The latter finding is contrary to earlier observations (Hagemann et al., 1997a). Here, we observed that ectopic expression of slr1588 did not restore the salt tolerance of the slr1588 mutant, making the essential function of this response regulator for salt tolerance questionable. Subsequent experiments showed that deletion of the entire coding sequence of slr1588 compromised the expression of the downstream situated ggpP gene, which encodes glucosylglycerol-phosphate phosphatase for synthesis of the primary osmolyte glucosylglycerol. Mutation of slr1588 by deleting the N-terminal part of this protein (∆slr1588-F976) did not affect ggpP expression, glucosylglycerol accumulation as well as salt-tolerance, while the mutation of ggpP resulted in the previously reported salt sensitive phenotype. In the ∆slr1588-F976 mutant spsA was up-regulated but sucrose content was lowered due to increased invertase activity. Our results reveal that Slr1588 is acting as a repressor for spsA as previously suggested but it is not crucial for the overall salt acclimation of Synechocystis.